ChemInform Abstract: Transition‐Metal‐Free Tunable Chemoselective N Functionalization of Indoles with Ynamides. Issue 5 (February 2015) - Hentz, Alexandre; Retailleau, Pascal; Gandon, Vincent; Cariou, Kevin; Dodd, Robert H.
Abstract Two new reaction pathways of ynamides with heterocycles containing a N‐unsubstituted pyrrole unit are developed using NaOtBu as the base.